Pemberdayaan Teknologi Tepat Guna Melalui Pelatihan Pembuatan Website - M. Nahdi Masruri; Rosyidil Ikhrom; Maisraoh; Dewi Puspita Sari (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2026)
This community service activity was carried out to increase the digital capacity and expand the market reach of Langgeng Jaya Abadi's MSMEs through the application of appropriate technology in the form of website creation and management training. This activity was designed in several stages, including needs identification, outreach, technical training, mentoring, and evaluation. The training included account creation on a free platform, template selection, product content creation, and management of supporting features such as photo galleries, contact information, and social media integration. A participatory approach was used to ensure active participant involvement throughout the process. The results showed that after the training, all participants were able to create a simple Google Site-based website and began using it for promotions. Identified direct impacts included increased product visibility in online media, increased orders, more sophisticated product branding, and increased demand from outside previously difficult-to-reach areas. Furthermore, this activity also encouraged a shift in marketing patterns from conventional methods to technology-based strategies. The long-term implications of this program include building a strong foundation of digital literacy, opportunities for website integration with e-commerce, and broader market access. It is recommended that this program be replicated in other MSMEs, with adaptations to local needs and ongoing mentoring to ensure the results are maintained and further developed. Kegiatan pengabdian kepada masyarakat ini dilaksanakan untuk meningkatkan kapasitas digital dan memperluas jangkauan pasar UMKM Langgeng Jaya Abadi melalui penerapan teknologi tepat guna berupa pelatihan pembuatan dan pengelolaan website. Kegiatan ini dirancang dalam beberapa tahap antara lain identifikasi kebutuhan, sosialisasi, pelatihan teknis, pendampingan, serta evaluasi. Pelatihan mencakup pembuatan akun pada platform gratis, pemilihan template, pengisian konten produk, dan pengelolaan fitur pendukung seperti galeri foto, informasi kontak, serta integrasi dengan media sosial. Pendekatan partisipatif digunakan untuk memastikan keterlibatan aktif peserta dalam seluruh proses. Hasil kegiatan menunjukkan bahwa setelah pelatihan, seluruh peserta mampu membuat website sederhana berbasis Google Site dan mulai memanfaatkannya untuk promosi. Dampak langsung yang teridentifikasi antara lain peningkatan visibilitas produk di media daring, peningkatan pesanan, terbrandingnya produk dengan lebih rapih serta adanya permintaan dari luar wilayah yang sebelumnya sulit dijangkau. Selain itu, kegiatan ini juga mendorong perubahan pola pemasaran dari metode konvensional ke strategi berbasis teknologi. Implikasi jangka panjang dari program ini adalah terbangunnya fondasi literasi digital yang kuat, peluang integrasi website dengan e-commerce, dan terbukanya akses pasar yang lebih luas. Program ini direkomendasikan untuk direplikasi pada UMKM lainnya dengan adaptasi sesuai kebutuhan lokal, disertai pendampingan berkelanjutan agar hasil yang dicapai dapat dipertahankan dan dikembangkan.